Analysis of LoRaWAN security echanism - Xiaobo YU; Hongru ZHU; Dapeng LIU; Qing AN (Dianxin kexue)
LoRaWAN is one of the most important low power WAN technologies.As LoRaWAN technology is massively applied in various vertical industries,network security becomes more and more important.The security mechanism of LoRaWAN technology was analyzed.In addition,the comparative analysis of similar schemes was carried out.The future research direction of LoRaWAN security mechanism was also pointed out.